Unseen Divorce and Wife Abandonment: The Urgency of Legal Assistance for Women in Guyangan Village, Bangsri District, Jepara Regency - Muhammad Umamuddin; Ika Dewi Nurmayani; Wahidullah Wahidullah (Universitas Negeri Gorontalo, 2025)
Legal assistance for women who are victims of cerai ghaib (unilateral, unregistered divorce) in Guyangan Village, Bangsri District, Jepara Regency constitutes a normative imperative to ensure the protection of women’s rights in divorce proceedings. This article aims to: (1) describe the forms and stages of legal assistance provided to women abandoned by their husbands without lawful divorce procedures; (2) analyse changes in the victims’ level of understanding of their legal rights; and (3) formulate prescriptive measures to strengthen legal protection for women in cerai ghaib cases at the village level. The community service activities were carried out through legal education on Islamic family law and positive law, individual legal counselling, and both litigation and non‑litigation assistance, including the drafting of divorce petitions and the preparation of supporting documents. Evaluation was conducted qualitatively through observation, interviews, and pre‑ and post‑assessments of the victims’ understanding of their legal rights. The results indicate a significant increase in women’s knowledge of lawful divorce procedures, rights to maintenance, child custody, and the mechanisms for filing divorce suits, which in turn encouraged some victims to pursue formal legal remedies. Prescriptively, the article recommends the institutionalisation of village‑based legal aid services, community paralegal training, and mandatory synergy among village government, religious institutions, and legal aid organisations to prevent the recurrence of cerai ghaib practices and to strengthen the protection of women’s rights in Guyangan Village.